Enhancing Students' Writing Skills for Recount Texts with the Use of Image Series as Media - Fatchur Roichan Manaf; Sulistyaningsih Sulistyaningsih (Jurnal Inspirasi Pendidikan, 2024)
The purpose of this research is to find out whether the use of series of pictures is effective and can also help students in speaking about recount text. This research was conducted on eleventh grade MA students. Putri Nurul Masyithoh Lumajang in the 2023/2024 academic year. This study employs qualitative approach. Pre-test, treatment, and post-test use a quantitative approach. The instrument in this research is speaking practice which is related to the topic of retelling the students holiday that has been taken. The research results show that a series of pictures can help students write about recount text and make the class more enjoyable. This research involved 22 class XI students from MA. Putri  Nurul Masyithoh Lumajang. The results showed that the average pre-test score was 63.3 and the average post-test score was 84.9 so the value above the minimum compliteness criteria. The average score on the post-test is higher than on the pre-test. Thus, the speaking ability of eleventh grade students at MA Putri Nurul Masyithoh Lumajang can be significantly improved by using a series of pictures.